Cardioprotective Effects of the Polyphenol Hydroxytyrosol from Olive Oil - Tejada, Silvia; Pinya, Samuel; del Mar Bibiloni, Maria; A. Tur, Josep; Pons, Antoni; Sureda, Antoni (Current Drug Targets, 2017)
Background: The Mediterranean diet includes olive oil as its primary source of fat. This diet is frequently associated to longevity and a lower incidence of chronic diseases due to its biological activities and health effects. Apart from oleic acid, olive oil contains many bioactive components including polyphenols that have been reported to exert antioxidant and anti-inflammatory activities. Polyphenols may almost in part be responsible for the protective effects against cardiovascular diseases associated with olive oil. Objective: To review and discuss the available literature on hydroxytyrosol effects as a cardioprotective agent. Moreover, we also discuss the chemistry, nutritional aspects and bioavailability of hydroxytyrosol. Results: Hydroxytyrosol is one of the major phenolic compounds in olive oil and has demonstrated strong radical-scavenging properties. Several studies have been performed in order to look further into the effects of the polyphenol hydroxytyrosol in relation to cardiovascular events and illnesses in animal trials and in vitro. However, no clinical trials have focused on the specific action of hydroxytyrosol and cardiovascular diseases, although some are being undertaken to look at olive oil or olive leaf extract properties. Conclusion: Hydroxytyrosol from olive oil exerts antioxidant, anti-inflammatory, anti-platelet aggregation and ati-atherogenic activities in in vitro and animal models. However, its possible therapeutic use in humans requires additional clinical trials.
Keywords: antioxidant